Modern Weapons and Military Equipment for Issue 2-2015 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The first flight of the military version of the helicopter EC645T2; Raytheon performing flight tests of a new generation of jammers; The first flight of the Russian Mi-171A2; Maiden flight of  the third prototype of the Indian Light Combat Helicopter; Tests of British weapons for F-35B; Progress and delays in the development of India's light fighter Tejas; Russian naval combat helicopter Ka-52K performed the first flight; IAF’s Mi-26 helicopter accomplished the first landing at high altitude; Iran unveiled a new version of the domestic light fighter; Saab offered Sea Gripen to Brasil; Airbus and KAI develop a light helicopter gunship in South Korea.